Managing the Training Process in Combat Sports (1998)
The Second Express Scientific Conference organized by the Combat Sports Department of Academy of Physical Education in Cracow, Saturday, 26 June 1999 SUMMARIES PROFESSIONAL ACTIVITIES OF WRESTLING AND GYMNASTICS COACHES LEADERSHIP STYLES IN SPORT THE CONDUCTING OF PSYCHOLOGICAL TRAINING ON FENCERS THE INFLUENCE OF PHYSICAL FITNESS AND PSYCHO-MOTOR ABILITIES ON FENCER'S RESULTS IN COMPETITIONS A COMPARISON OF THE BODY'S WORKLOAD DURING TRAINING AND COMPETING IN THE PARAOLYMPICS EFFECT OF ALTITUDE TRAINING ON CHANGES IN SELECTED BLOOD BIOCHEMICAL PARAMETERS IN MALE AND FEMALE JUDOISTS INFLUENCE OF CHOSEN SOMATIC INDEXES ON TRAINING OF HIGH CLASS JUDO SPORTSMEN BLOOD LACTATE DYNAMICS FOLLOWING A JUDO CONTEST LEVELS OF ANAEROBIC AND AEROBIC CAPACITY INDICES AND RESULTS FOR THE SPECIAL FITNESS TESTING JUDO COMPETITORS INFLUENCE OF THE APPLIED TRAINING LOADS ON THE LEVEL OF SPECIAL FITNESS LEVEL OF JUDO COMPETITORS DIFFERENTIATION BETWEEN HIGH CLASS JUDOISTS IN TERMS OF INDEXES OF EXPERIENCE, PHYSICAL DEVELOPMENT, PSYCHOMOTOR FITNESS AND THEIR ACTIVITIES DURING COMPETITIONS WORK LOADS IN WRESTLING IN THE PERIOD FROM 1988 TO 1996 - AN ATTEMPT OF DIAGNOSIS THE VALIDITY OF PLASMA CREATINE KINASE (CK) ACTIVITY DETERMINATION IN MONITORING OF WRESTLER'S TRAINING CRITERIA FOR IDENTIFICATION OF COMBAT SPORTS ONTOGENESIS OF BUDO MASTER. PROGRESSIVE DEVELOPMENT ON THE MARTIAL ARTS WAY INTEGRATED SYSTEM OF TRAINING PROCESS MANAGEMENT OF THE LEADER OF OPEN CATEGORY RAFA£ KUBACKI SPORT CLUB AZS-AWF WROC£AW, JUDO SECTION THE VALUE OF COACHES' VALUES: A CROSS-CULTURAL SURVEY DIFFERENCES IN THE LEADING AND SOLVING A FIGHT THE FREE - STYLE WRESTLERS IN THE DIFFERENT GROUP OF AGE TECHNIQUE OF ATTACK OF THE BEST AMATEUR BOXERS OF THE WORLD AND EUROPE BOXING TRAINING SIMULATOR APPLICATION IN MARTIAL SPORTS EVALUATION OF POLISH POLICE OFFICERS' FITNESS DEVELOPMENT TRENDS IN WOMEN'S JUDO IN THE LIGHT OF THE RESULTS OF FIGHTS DURING THE ATLANTA OLYMPIC GAMES TRAINING TENDENCIES IN JUDO ON THE GROUND OF ANALYSIS OF FIGHTS OF SENIOR COMPETITORS DIFFERENCES IN THE TOURNAMENT ACTIVITY OF WOMEN AND MEN PRACTISING JUDO COMPARISON OF SKILL RANGE BETWEEN OLYMPIC AND WORLD JUDO MEDALLISTS PHYSIOTHERAPY PROCEDURE WITH REGARD OF THE TYPE OF BODY INJURIES IN JUDO STREAMLINING THE SCHEDULE OF TECHNICAL AND TACTICAL SCHOOLING OF JUNIOR JUDOISTS TIME AND MATERIAL STRUCTURE IN JU-JITSU SPORTS COMBAT REGISTRATION AND ANALYSIS OF TAEKWON-DO FIGHT ESSENCE (ITF VERSION) COMPETITION RESULTS AND ATTEMPTS AT FORESEEING SPORTS ACHIEVEMENTS IN JUDO GRADED SPECIAL FITNESS JUDO TEST